Mapeamento de stakeholders nas áreas conexas de turismo e meio ambiente: um estudo em João Pessoa/PB - Delgado, Anna Karenina Chaves (2011)
The present study aims to understand the perception in a manager perspective of the relationship between the stakeholders of tourism and environmental management in João Pessoa (PB). It is a qualitative, transversal, descriptive and exploratory research, held with keys stakeholders of tourism and environment in the capital of Paraíba. The data were collected through structured interviews and the analysis of the minutes of the municipal council of tourism, called COMTUR/ JP. The data research allowed us to affirm that the environmental stakeholders have a higher academic background than those of tourism, on the other hand the tourism stakeholders‟ have longer experience time than the environmental stakeholders‟. In general, the use of environmental resources for tourism is noticed as positively by the tourism stakeholders‟ and as intermediate for the environmental stakeholders‟, the tourism development is consider to be a non predatory active in João Pessoa, but it is very concentrate in the coastal area, the remnants of Atlantic Forest or protected areas are not used for tourism. The main environmental impacts cause by tourism according to the stakeholders interviewed (tourism and environment) were the environmental degradation of reef, beach pollution and the construction of tourism facilities in areas that should be protected, however, there was a stakeholder who believes that the tourism development in Paraíba is so nascent that it is unable to impact the environment. The performance of SETDE, PBTUR and SUDEMA was consider inconsistent by some of the interviewed stakeholders‟. The NGO representatives believe that the most important thing is a paradigm shift from the entrepreneurs and the local population. Despite the apparently close relationship between tourism and environment management in João Pessoa (PB), some actions of tourism agencies and the state government has left some unhappy important environmental stakeholders indicating that the relationship between tourism and environment in the city is becoming tenser each year